Analisa Inkubasi Desa Wisata Kabupaten Garut Melalui Icon Produk dan Digital Marketing - Hani Siti Hanifah; Marissa Disthy Putri; Dwirani Fauzi Lestari; Yosep Septiana (Institut Teknologi Garut, 2026)
Tourism village development is an important strategy for improving the economy and welfare of rural communities through professional, effective, and sustainable tourism destination management. Sustainable tourism is expected to reduce poverty, minimize social inequality, strengthen village development funding, and maintain public order. However, the success of tourism village development greatly depends on the synergy of village institutions, particularly in the implementation of Village-Owned Enterprise (BUMDes) policies, both in terms of strengthening product icons and digital marketing. This study uses a qualitative approach. Primary data were obtained through interviews with BUMDes managers, MSME actors, tourism village managers, and the Village Community Empowerment Agency (BPMD) in Garut Regency, while secondary data were sourced from literature, journals, and relevant websites. The research population included tourism villages and legally registered BUMDes in Garut Regency, with a sample consisting of six tourism villages, 30 respondents, and four informants selected using purposive sampling. Data validity was tested using triangulation techniques. The results show that tourism village development through digital marketing, product icons, and tourism village incubation approaches achieved varying outcomes. The implementation of digital marketing and product icon development remains suboptimal, as indicated by the limited use of digital platforms and the lack of competitive flagship products. In contrast, the tourism village incubation aspect is relatively better, reflected in the fairly well-organized BUMDes organizational structure and relatively active community involvement, although it has not yet been formally accumulated. Therefore, collaboration among stakeholders needs to be strengthened in order to realize sustainable and competitive tourism villages.